REDEFINING FREEDOM OF RELIGION FOR CHILDREN AS DEPICTED IN THE MOVIE OF ARE YOU THERE GOD? IT’S ME, MARGARET: A POSTMODERN APPROACH - Irianti, Danika Rahma; Munjid, Achmad (Pengkajian Amerika, Universitas Gadjah Mada, 2025)
The author frequently observed parents embroiled in a continuous argument regarding the appropriate religious upbringing of their children, which seem to be an ongoing and persistent disagreement to this day. The matter then inspired the researcher to find out more regarding the religious freedom for children, especially in the United States, as seen in the movie version of Are You There God? It's Me, Margaret. In relation to the previous statement, this article formulates two objectives: (1) to present how the movie depicts the kinds of children’s freedom of religion, and (2) to discuss how the findings of the first objective contribute to the ongoing polemic in the United States. The postmodernism approach was applied, by using Lyotard’s theory, focusing on the diversity of experiences and the rejection of grand narrative as its starting point to unveil the fragmented freedom of religion for children in the US. The first results show that, according to the movie, two types of parents often engage in a debate: one who creates a religion-neutral environment and the other who creates a religion in a neutral environment. The second result shows that both types are valid. Unlike the freedom of religion for children, the freedom of religion of parents is, in a way, stronger than the rights of children. The powerful parental right is legitimate if parents do not break the border upon “the best interest of the children”. Parents are then allowed to impart or not to impart their religious beliefs towards their children.